The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ajpa.24231
|View full text |Cite
|
Sign up to set email alerts
|

Sex estimation of teeth at different developmental stages using dimorphic enamel peptide analysis

Abstract: Objectives: This study tests, for the first time, the applicability of a new method of sex estimation utilizing enamel peptides on a sample of deciduous and permanent teeth at different stages of mineralization, from nonadults of unknown sex, including perinates. Materials and methods: A total of 43 teeth from 29 nonadult individuals aged from 40 gestational weeks to 19 years old were analyzed. The sample included pairs of fully mineralized and just developing teeth from the same individual. The individuals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
(69 reference statements)
0
34
0
3
Order By: Relevance
“…Most archeological studies do not have estimates for juvenile sex. Still, with the advent of the use of enamel peptide analysis for sex determination in children (Gowland et al, 2021), the landscape of the study of childhood sex differences in these lesions may change dramatically over the next decade.…”
Section: Pathways To Sex Differences In Indicators Of Childhood Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Most archeological studies do not have estimates for juvenile sex. Still, with the advent of the use of enamel peptide analysis for sex determination in children (Gowland et al, 2021), the landscape of the study of childhood sex differences in these lesions may change dramatically over the next decade.…”
Section: Pathways To Sex Differences In Indicators Of Childhood Stressmentioning
confidence: 99%
“…Most archeological studies do not have estimates for juvenile sex. Still, with the advent of the use of enamel peptide analysis for sex determination in children (Gowland et al, 2021), the landscape of the study of childhood sex differences in these lesions may change dramatically over the next decade. However, similar to the contemporary autopsy sample used here, the few bioarchaeological studies fortunate enough to have some sex estimates for deceased children also find male biases in lesion frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This study emphasizes the importance of estimating sex in juveniles in past populations, which is now possible at reasonable cost using amelogenin peptide analysis (Stewart et al, 2016 , 2017 ). Tests of this method on developing dentition has now shown that it can be used to consistently and reliably estimate sex in juveniles as young as perinate (Gowland et al, 2021 ; Stewart et al, 2017 ). As this method grows in popularity, we urge bioarchaeologists studying growth to make use of it to explore sex‐based differences in growth attainment within their study populations.…”
Section: Discussionmentioning
confidence: 99%
“…These osteological observations may be supplemented by information from proteomics, ancient DNA (amelogenin gene), and observations of mummified soft tissues, when available. The persistently elusive goal of accurate biological sex determinations in juveniles appears imminently achievable through minimally invasive proteomic procedures (Buonasera et al, 2020; Gowland et al, 2021; Parker et al, 2019; Stewart et al, 2017; Ziganshin et al, 2020) and genetic analyses (Mittnik et al, 2016; Skoglund et al, 2013). Efforts to improve macroscopic approaches to sex estimation in juveniles also continue (e.g., Garvin et al, 2021; Stull et al, 2017).…”
Section: Inferring Ancient Identitiesmentioning
confidence: 99%